colonization and/or infection during infancy and the risk of childhood allergic diseases - Sun Hwa Lee; Yun Na Gong; Eell Ryoo (Korean Pediatric Society, 2017)
PurposeThe gut microbiota can influence several diseases through immune modulation; however, the exact role of microbes such as Clostridium difficileand the relationship between microbiota colonization and allergic diseases are not well known. This study aimed to determine the relationship between C. difficilecolonization and/or infection (CDCI) during infancy and allergic diseases during early childhood.MethodsInfants 1-12 months of age presenting changes in bowel habits for more than 2 weeks were enrolled in this study. After dividing them into 2 groups according to the presence and absence of C. difficile, the risk of allergic disease development during childhood was identified and compared.ResultsSixty-five patients were included in this study; 22 (33.8%) were diagnosed with CDCI. No significant differences were observed in baseline characteristics between the C. difficile-positive and -negative groups except for antibiotic exposure (22.7% vs. 60.5%, P=0.004). Compared to the C. difficile-negative group, the risk of developing at least one allergic disease was higher in the C. difficile-positive group after adjusting other variables (adjusted odds ratios, 5.61; 95% confidence interval, 1.52-20.74; P=0.007). Furthermore, food allergies were more prevalent in the C. difficile-positive group (P=0.03).ConclusionCDCI during infancy were associated with a higher risk of developing allergic diseases during early childhood. These results suggest that CDCI during infancy might reflect the reduced diversity of the intestinal microbiota, which is associated with an increased risk of allergic sensitization. To identify the underlying mechanism, further investigation and a larger cohort study will be needed.